PEMIKIRAN EKONOMI IBNU QAYYIM TENTANG KONSEP TAS’IR - Wahyu, A. Rio Makkulau (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Ibn Qayyim Al-Jauziyyah is an Islamic thinker who examines various issues which are meant in the economic field which are contained in his various works such as; in At-Thuruq Hukmiyah Fi As-Siyasati Asy-Syariyah. This book explains about a guideline of government in set a state policy. Ibnu Qayyim in his book divided pricing policy into 2 kinds those are fair pricing policy and legal and also unfair pricing policy and it is prohibited. This study is conducted by using library research method with the purposes to describe the thoughts of Ibn Qayyim about pricing policy. Analysis result showed that fair pricing policy in market mechanism has been main guidelines in every its transaction. Fair pricing by government is very suggested when the situation in market undergoes disorganisation thus make many bad impacts for trader, this the government’s role as wilayatul hisbah in determining price in market for realising prosperity.